Increased expression of stefin B in the nucleus of T98G astrocytoma cells delays caspase activation - Sun, Tao; Turk, Vito; Turk, Boris; KOPITAR-JERALA, Natasha (Frontiers in Molecular Neuroscience, 2012)
Stefin B (cystatin B) is an endogenous inhibitor of cysteine proteinases localized in the nucleus and the cytosol. Loss-of-function mutations in the stefin B gene (CSTB) gene were reported in patients with Unverricht-Lundborg disease (EPM1). Our previous results showed that thymocytes isolated from stefin B-deficient mice are more sensitive to apoptosis induced by the protein kinase C inhibitor staurosporin (STS) than the wild-type control cells. We have also shown that the increased expression of stefin B in the nucleus of T98G astrocytoma cells delayed cell cycle progression through the S phase. In the present study we examined if the nuclear or cytosolic functions of stefin B are responsible for the accelerated induction of apoptosis observed in the cells from stefin B-deficient mice. We have shown that the overexpression of stefin B in the nucleus, but not in the cytosol of astrocytoma T98G cells, delayed caspase-3 and-7 activation. Pretreatment of cells with the pan-caspase inhibitor z-Val-Ala-Asp(OMe)-fluoromethylketone completely inhibited caspase activation, while treatment with the inhibitor of calpains- and papain-like cathepsins (2S,3S)-trans-epoxysuccinyl-leucylamido-3-methyl-butane ethyl ester did not prevent caspase activation. We concluded that the delay of caspase activation in T98G cells overexpressing stefin B in the nucleus is independent of cathepsin inhibition.